Hypertension and left ventricular hypertrophy - Aronow, Wilbert S. (Annals of Translational Medicine; Vol 5, No 15 (August 06, 2017): Annals of Translational Medicine (Focus on “Myokines, Exercise and Cardiovascular Disease”), 2017)
Left ventricular hypertrophy (LVH) is an abnormal increase in left ventricular mass. which is a marker for and contributes to coronary events, stroke, heart failure, peripheral arterial disease, and cardiovascular mortality in patients with hypertension (1-12). LVH is commonly measured by electrocardiography, echocardiography, and magnetic resonance imaging Concentric LVH is an increased left ventricular mass index with a relative wall thickness ≥0.45 (1). Eccentric LVH is an increased left ventricular mass index with a relative wall thickness